Natural Convection Heat Transfer of Ag-MgO/Water Micropolar Hybrid Nanofluid inside an F-shaped Cavity Equipped by Hot Obstacle - Rasul Mohebbi; Abbas Abbaszade; Mahsa Varzandeh; Yuan Ma (Journal of Heat and Mass Transfer Research, 2021)
This paper presents a series of numerical simulations of nanofluid natural convection inside an F-shaped enclosure equipped by heat source. A hybrid nanofluid consisting of Ag and MgO nanoparticles and water as base fluid was used. Lattice Boltzmann method (LBM) was applied and the effects of Raleigh number (103 ≤ Ra ≤ 106), solid volume fraction of nanoparticle (0 ≤ ϕ ≤ 0.02), and heat source location (0 ≤ S ≤ 0.9) on the flow field, distribution of temperature and heat transfer performance were analyzed according to streamlines, isotherms, and profiles of average Nusselt numbers. The results indicated that the average Nusselt number enhances by increasing the ϕ, although the addition of nanoparticles cannot change the flow pattern and the thermal field significantly. At low Ra, the effect of Ra on average Nu is weak. However, for high Ra, the heat transfer increases significantly by increasing the Ra. The position of heat source also affects the average Nu. The S = 0.6 is the best position of the hot obstacle for enhancing the heat transfer and S = 0.9 is the worst choice. This trend cannot be affected by Ra and ϕ.